2021
DOI: 10.3390/ijerph18168257
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults with Hypertension: Prevalence of Falls and Their Associated Factors

Abstract: Falls are prominent health issues among older adults. Among hypertensive older adults, falls may have a detrimental effect on their health and wellbeing. The purpose of this study is to determine the prevalence of falls among hypertensive older adults and to identify the associated factors that contribute to their falls. This was a cross-sectional study conducted among two hundred and sixty-nine hypertensive older adults who were selected via systematic random sampling in two primary health clinics in Kuala Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
1
13
0
1
Order By: Relevance
“…The study revealed that hypertension was a significant intrinsic factor associated with fatal falls, constituting the highest proportion (11.33%) among reported cases of fatal falls with medical conditions. This finding is consistent with previous studies indicating that older adults with cardiovascular disease, particularly hypertension, face an elevated risk of falls 10 , 16 , 17 . One possible explanation for this increased risk among older individuals with hypertension is the presence of gait and balance disorders.…”
Section: Discussionsupporting
confidence: 93%
“…The study revealed that hypertension was a significant intrinsic factor associated with fatal falls, constituting the highest proportion (11.33%) among reported cases of fatal falls with medical conditions. This finding is consistent with previous studies indicating that older adults with cardiovascular disease, particularly hypertension, face an elevated risk of falls 10 , 16 , 17 . One possible explanation for this increased risk among older individuals with hypertension is the presence of gait and balance disorders.…”
Section: Discussionsupporting
confidence: 93%
“…They also had higher rates of administration of polypharmacy. The influence of polypharmacy as a risk factor predicting falls in the old age people has been previously documented in the literature ( 32 , 33 ). Yet, the effect of polypharmacy on the occurrence of fall was not confirmed in the current study multivariate analysis.…”
Section: Discussionmentioning
confidence: 89%
“…Another thing about the BMI in the obesity category was that people with excess weight tend to have difficulty moving freely to be able to move freely. It takes much energy to vascularize body tissues, and the heart must pump blood and increase pressure in the body's blood vessels [18,19] . smoking is not associated with cardiometabolic conditions.…”
Section: Discussionmentioning
confidence: 99%